2015
DOI: 10.1530/erc-15-0452
|View full text |Cite
|
Sign up to set email alerts
|

Future directions in the diagnosis and medical treatment of adrenocortical carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare disease with a poor prognosis. Discrimination between ACCs and adrenocortical adenomas (ACAs) remains challenging, with the current gold standard being the Weiss score, consisting of several histopathological characteristics. However, new markers like Ki67, a marker for proliferation, and the staining of reticulins are promising not only as it comes to identifying malignancy but also as prognostic markers in patients with ACC. Currently, surgery is still the only curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 236 publications
(232 reference statements)
1
65
0
4
Order By: Relevance
“…In this study, we confirmed that IGF2 is an important marker for ACC, but as also previously described in a number of studies, does not fully discriminate ACCs from ACAs (Creemers et al 2016). Mean sensitivity and specificity for diagnosing malignancy are both around 80%, with substantial variances between studies.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we confirmed that IGF2 is an important marker for ACC, but as also previously described in a number of studies, does not fully discriminate ACCs from ACAs (Creemers et al 2016). Mean sensitivity and specificity for diagnosing malignancy are both around 80%, with substantial variances between studies.…”
Section: Discussionsupporting
confidence: 87%
“…A key molecular event that contributes to ACC formation and aggressiveness is the constitutive activation of the Wnt/ÎČ-catenin signaling pathway due to mutation of the CTNNB1 gene [2,3]. Approximately 50% of ACC in adults are hormone-secreting tumors that produce cortisol (Cushing's syndrome) or androgen or multiple steroids [4].…”
Section: Introductionmentioning
confidence: 99%
“…ACC is a rare endocrine malignancy with a high risk of relapse and metastatization even when the primary tumor is diagnosed and surgically removed at an early stage (Else et al 2014, Creemers et al 2016. Current treatments for ACC have only a limited efficacy when disease is at an advanced stage and rely upon use of the adrenolytic agent mitotane (Terzolo et al 2007) and of combination chemotherapy in patients with progressive disease .…”
Section: Metastasis In Adrenocortical Carcinoma (Acc): Do Paradigms Amentioning
confidence: 99%
“…The cornerstone for the treatment of metastatic disease is mitotane (o,pâ€Č-DDD), a drug provided with both antihormonal and antitumoral activities (Terzolo et al 2007, Else et al 2014, Creemers et al 2016). This compound is commonly associated with EDP polychemotherapy in patients with rapidly progressive disease, but this regimen does not substantially improve OS of patients .…”
Section: Perspectivesmentioning
confidence: 99%